Two roads diverged: Two alternate strategies for protecting captive freight shippers in the "Americas" model of freight rail restructuring - Russell W. Pittman (U.S. Department of Justice, Antitrust Division, Expert Analysis Group (EAG), 2024)
How to protect "captive shippers" from monopolistic abuses by a railway? In an "open access" system, it's straightforward: provide infrastructure access to a competing train operating company. In a system without open access - as in, for example, the United States, Canada, Mexico, and Brazil - it's not so straightforward. For freight shippers lacking economic intramodal or intramodal shipping alternatives, regulators and policymakers have focused on regulatory alternatives in two broad categories: 1) direct regulation of rates, and 2) imposed, regulated competition from a second railway (for example, interswitching or trackage rights). We argue that, despite disadvantages familiar to every Economics 101 student, direct regulation of rates has proven to be the superior alternative, and we discuss alternative mechanisms currently under debate.
Keywords: L51; L92; L98; 330; freight railways; regulation; captive shippers; Canada; Mexico